Optimal loading dose for the initiation of warfarin: a systematic review - Heneghan, C; Tyndel, S; Bankhead, C; Wan, Y; Keeling, D; Perera, R; Ward, A (BioMed Central, 2010)
Background: Selection of the right warfarin dose at the outset of treatment is not straightforward, and current evidence is lacking to determine the optimal strategy for initiation of therapy. Methods: We included randomized controlled trials in patients commencing anticoagulation with warfarin, comparing different loading dose or different regimens. We searched Medline, EMBASE, the Cochrane Library and the NHS Health Economics Database up to June 2009. Primary outcomes were time to stable INR and adverse events. We summarised results as proportion of INRs in range from date of initiation and compared dichotomous outcomes using relative risks (RR) and calculated 95% confidence intervals (CIs). Results: We included 11 studies of 1,340 patients newly initiated on warfarin. In two studies that used single INR measures, a loading dose of 10 mg compared to 5 mg led to more patients in range on day five. However, in two studies which measured two consecutive INRs, a loading dose of 10 mg compared to 5 mg did not lead to more patients in range on day five (RR = 0.86, 95% CI, 0.62 to 1.19, p = 0.37). Patients receiving a 2.5 mg initiation does took longer to achieve the therapeutic range, whilst those receiving a calculated initiation dose achieved target range 0.8 days quicker (4.2 days vs. 5 days, p = 0.007). More elderly patients receiving an age adjusted dose achieved a stable INR compared to the Fennerty protocol (48% vs. 22% p = 0.02) and significantly fewer patients on the age adjusted regimens had high out-of-range INRs. Two studies report no significant differences between genotype guided and 5 mg or 10 mg initiation doses and in the one significant genotype study the control group INRs were significantly lower than expected. Conclusion: Our review findings suggest there is still considerable uncertainty between a 10 mg and a 5 mg loading dose for initiation of warfarin. In the elderly, lower initiation doses or age adjusted doses are more appropriate, leading to less higher INRs. Currently there is insufficient evidence to warrant genotype guided initiation, and adequately powered trials to detect effects on adverse events are currently warranted.